Iptkalim inhibits cocaine challenge-induced enhancement of dopamine levels in nucleus accumbens and striatum of rats by up-regulating Kir6.1 and Kir6.2 mRNA expression. - Liu Yun; He Hai-Rong; Ding Jian-Hua; Gu Bing; Wang Hai; Hu Gang (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effect and mechanism of novel ATP-sensitive potassium channel opener (KCO) iptkalim (IPT) on acute and cocaine challenge-induced alterations in the levels of dopamine (DA) and glutamate (Glu) from nucleus accumbens (NAc), striatum, and prefrontal cortex (PFC) in rats. METHODS: The levels of DA and Glu were assayed using high performance liquid chromatography (HPLC) combined with amperometric and fluorescent detection, respectively. The mRNA levels of Kir6.1, Kir6.2, SUR1, and SUR2 were measured by semiquantitative reverse transcription polymerase chain reaction (RT-PCR). RESULTS: IPT did not affect acute cocaine (30 mg/kg, ip)-induced elevations in either DA levels from NAc and striatum or Glu levels from NAc and PFC. An acute cocaine challenge (30 mg/kg, ip) on d 21 after withdrawal caused an elevation in DA levels in NAc and striatum. Moreover, the same treatment also increased Glu levels in PFC and NAc of cocaine-pretreated rats. Repeated IPT injections reversed cocaine challenge-induced DA increase in NAc and striatum. Cocaine challenge increased Kir6.1 and Kir6.2 mRNA expression in striatum and NAc and only elevate Kir6.2 expression in PFC in both cocaine-pretreated rats and rats pretreated with IPT plus cocaine. Moreover, expression of Kir6.1 and Kir6.2 mRNA was augmented in rats pretreated with IPT plus cocaine compared to rats pretreated with cocaine alone. No significant change was found in the SUR1 and SUR2 expression of all four groups. CONCLUSION: IPT inhibited cocaine challenge-induced enhancement of DA levels in NAc and striatum by up-regulating Kir6.1 and Kir6.2 mRNA expression.